2020
DOI: 10.3390/molecules25184144
|View full text |Cite
|
Sign up to set email alerts
|

Using Medicinal Plants in Valmalenco (Italian Alps): From Tradition to Scientific Approaches

Abstract: This ethnobotanical survey was carried out in Caspoggio (Valmalenco, SO, Italy) with the purpose of investigating the traditional uses of medicinal plants. Moreover, a bibliographic research meant to validate or refute the uses, focusing on the potentially responsible compounds, was performed. Fifty-nine species, attributable to 30 families (Asteraceae, Pinaceae, Malvaceae, and Lamiaceae the most cited), were mentioned. Arnica montana, anti-inflammatory for traumas and musculoskeletal pains; Pinus mugo, expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 222 publications
(152 reference statements)
5
44
0
Order By: Relevance
“…Since there are not many studies that calculate the exact amount of each compound of NVOCs in bamboo groves, it is challenging to compare measured values of this study with other bamboo grove-related prior studies but, compared to prior studies that measured NVOCs emitted by different types of forests with the same measurement methods, the amount of NVOC compounds detected in this study was found to be similar or higher than the values of preceding studies [28,29]. In particular, α-pinene, 3-carene, and camphene accounted for 70% of the total emissions, with α-pinene known to have anxiolytic, anti-inflammatory, antioxidant, and antiproliferative effects, while 3-carene is known to improve inflammatory conditions [14,[30][31][32][33]. Finally, camphene was found to have antiproliferative, antioxidant, antinociceptive, and antihyperlipidemic effects, along with the ability to enhance metabolic activities [34][35][36].…”
Section: Discussionsupporting
confidence: 79%
“…Since there are not many studies that calculate the exact amount of each compound of NVOCs in bamboo groves, it is challenging to compare measured values of this study with other bamboo grove-related prior studies but, compared to prior studies that measured NVOCs emitted by different types of forests with the same measurement methods, the amount of NVOC compounds detected in this study was found to be similar or higher than the values of preceding studies [28,29]. In particular, α-pinene, 3-carene, and camphene accounted for 70% of the total emissions, with α-pinene known to have anxiolytic, anti-inflammatory, antioxidant, and antiproliferative effects, while 3-carene is known to improve inflammatory conditions [14,[30][31][32][33]. Finally, camphene was found to have antiproliferative, antioxidant, antinociceptive, and antihyperlipidemic effects, along with the ability to enhance metabolic activities [34][35][36].…”
Section: Discussionsupporting
confidence: 79%
“…The above five substances have also been shown to be the main components of NVOC in several prior studies. In particular, α-pinene, 3-carene and camphene accounted for 70% of the total emissions, with α-pinene known to have anxiolytic, anti-inflammatory, antioxidant, and antiproliferative effects, and 3-carene is known to improve inflammatory conditions [13,[26][27][28][29]. Finally, camphene was found to have an antiproliferative, antioxidant, antinociceptive, and antihyperlipidemic effects, and also can enhance metabolism activities [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Plantain belongs to the Plantaginaceae family. It contains polysaccharides and polyphenols with antibiotic activity (122). Plantain leaves contain iridoid glycosides, flavonoids (luteolin), mucilage, tannins, pectins, and salic acid.…”
Section: Plantago Majormentioning
confidence: 99%